FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - JONATHAN JONATHAN; Riki Sanjaya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The research purpose is to investigate the relationship between several characteristics of the company to the firm value. These characteristics include managerial ownership, institutional ownership, capital structure, profitability, company growth, company size, and liquidity. This research uses a sample of companies using the purposive sampling method, there were 85 non-financial companies listed on the Indonesia Stock Exchange consistently from 2017 to 2019 which were the samples of this study. A multiple regression model was used in analyzing the data of this study.The results indicate that managerial ownership, institutional ownership, capital structure, profitability, firm growth, and liquidity influence firm value. While the size of the company does not affect the value of the company. Managerial ownership will reduce agency conflictt, institutional ownership will increase efective monitoring, capital structure, profitability, firm growth, and liquidity will give signal to investor so that several variabel would influence firm value.